Stability analysis of quantitative and qualitative traits in heritage rice landrace Zag (red rice) of Kashmir Himalayas - Khan, Gazala Hassan; Sofi, Najeebul Rehman; Shikari, Asif Bashir; Wani, Shabir Hussain; Khan, Raheel; Hussain, Ashaq; Mohiddin, Fayaz; Rahimi, Mehdi; Bhat, Nazir Ahmed (Journal of Cereal Research, 2021)
Eighteen red rice collections from different sites of the KashmirHimalayas valley were evaluated during kharif - 2017, 2018 and 2019 forstability performance for yield along with its related traits and cookingquality traits. The genotype effect had a significant mean square forall traits except panicle length based on analysis of variance. Thegenotype×environment interaction showed a significant differencefor some of the studied traits, which included kernel elongation ratio,grain yield, number of panicles, 1000 seed weight, kernel length beforecooking and kernel length after cooking. When the environment + (G× E) interaction is divided into environment (linear), G x E (linear) andcongruent deviation, the mean square by environment (linear) showsthat all attributes are taken into consideration. These results showed asignificant difference between the environments that can have a greatimpact on the expression of the studied traits. Similarly, G x E (linear)was observed to be significant for all traits except 50% floweringdays, plant height and maturity days, which means that the genotypebehaviour of these traits is environmentally predictable and indicatesthat this is the function of the components of the linear environment.Mean squares due to pooled deviation (nonlinearity) were significantfor all traits except 1000 grain weight and kernel breadth beforecooking, suggesting that nonlinear composition is important forcharacteristics that contribute to the total G×E interaction. Thus, thegenotypes differ significantly in terms of stability to the environmentfor such traits. C-5 has a low average for flowering days up to 50%and ripening days relative to the population mean, the row also hasa uniform regression coefficient and the least deviation from theregression of yield showing consistent behaviour of the stream overthe years. Likewise, C14 has a uniform regression coefficient and theleast deviation from the regression for yield as well as a low mean fordays up to 50% flowering and days until ripening, showed suitabilityof the line for consistent yield and early maturity.